Reimagining Islamic Education in India: Artificial Intelligence, Character Formation, and the Sustainable Development Goals in the Era of Society 5.0 - M. Neeharika (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2026)
The rapid advancement of digital technologies and the emergence of Society 5.0 have created new opportunities and challenges for educational institutions worldwide, including Islamic education in India. In this context, Islamic educational institutions are expected not only to adopt technological innovations but also to preserve their role in fostering ethical values, character development, and social responsibility. This study explores the transformation of Islamic education in India through the integration of artificial intelligence (AI), character formation, and the Sustainable Development Goals (SDGs) within the framework of Society 5.0. Employing a qualitative research approach, data were collected through in-depth interviews, observations, and document analysis involving educators, students, and educational administrators from selected Islamic educational institutions. The findings reveal that AI has enhanced learning accessibility, personalized instruction, and educational management, while character education remains central to nurturing integrity, responsibility, empathy, and ethical leadership among students. The study also demonstrates that the incorporation of SDG-related values encourages environmental awareness, social justice, community engagement, and sustainable citizenship. Furthermore, Islamic educational institutions increasingly view technological innovation and moral development as complementary rather than contradictory dimensions of education. The integration of AI, character formation, and sustainability principles contributes to a holistic educational model that prepares students to navigate technological advancements while maintaining strong ethical and spiritual foundations. The study concludes that reimagined Islamic education can serve as a strategic framework for developing technologically competent, morally grounded, and socially responsible graduates capable of contributing to sustainable development in the era of Society 5.0. These findings offer valuable insights for policymakers, educators, and researchers seeking to strengthen the relevance and impact of Islamic education in contemporary society.